TINGKAT KEAMANAN PROSEDUR STENT OLEH AHLI NEUROINTERVENSI DI INDONESIA - Fritz Sumantri Usman,1 Achmad Firdaus Sani, 2 Yuwono,3 Ashari Bahar,4 Condrad Mangapul Pasaribu,5 Ri (NEURONA, 2016)
INTRODUCTION STENTING PROCEDURE HAS BEEN DEVELOPED AND WIDELY USED NOWADAYS SINCE THE NUMBER OF CEREBROVASCULAR DISEASE KEEP INCREASED THE GOAL OF STENT PLACEMENT IS TO PREVENT RECURRENT STROKE STENTING IS EXPECTED TO BE MORE EFFECTIVE IN SECONDARY PREVENTION OF STROKE MANAGEMENT RATHER THAN MEDICAL THERAPY ALONE HOWEVER THIS PROCEDURE HAS SOME COMPLICATION AT RISK EITHER REVERSIBLE OR PERMANENT EVEN DEATH